RECONCILE THE RELIGION AND SCIENCE EDUCATION MANAGEMENT IN ISLAM - Syamsul Kurniawan (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This research is aimed to reconcile science and religion, and to seek its relevance in the management of non-dichotomous Islamic education.In addition, this research departs from the researcher’s anxiety in response to the dichotomous thought between religion and science which in turn manifests in the separation of science and religion in the history of Islamic education management. This results in the current Islamic education that suffers a setback in the development of science. Therefore, in the management of Islamic education, reintegration needs to be done without any dichotomy between religion and science.